Hepcidin and Iron Homeostasis in Patients with Subacute Thyroiditis and Healthy Subjects. (27th February 2019) - Hernik, Aleksandra; Szczepanek-Parulska, Ewelina; Filipowicz, Dorota; Czarnywojtek, Agata; Wrotkowska, Elżbieta; Kramer, Lucyna; Urbanovych, Alina; Ruchała, Marek
Abstract : Purpose . Hepcidin is an acute-phase protein involved also in regulation of iron homeostasis. The aim of the study was to prospectively assess for the first time the hepcidinEL concentration in patients with subacute thyroiditis (SAT), to identify biochemical determinants of hepcidinEL concentration and evaluate the potential role of hepcidin in SAT diagnosis and monitoring. Methods . Out of 40 patients with SAT initially recruited, restrictive inclusion criteria fulfilled 21 subjects aged45 ± 10 years and 21 healthy control subjects (CS). HepcidinEL concentration, thyroid status, and iron homeostasis were evaluated at SAT diagnosis and following therapy and compared with CS. Results . The median hepcidinEL concentration at SAT diagnosis is higher than that in CS (48.8 (15.9-74.5) ng/mL vs. 18.2 (10.2-23.3) ng/mL, p = 0.009 ) and is significantly lower after treatment (4.0 (1.2-10.0) ng/mL, p = 0.007 ) compared with CS. The ROC analysis for hepcidinEL at SAT diagnosis revealed that area under the curve (AUC) is 0.735 (p = 0.009 ), and the cut-off for hepcidinEL concentration is 48.8 ng/mL (sensitivity 0.52 and specificity 0.95). HepcidinEL in SAT patients correlated with CRP (r = 0.614, p = 0.003 ), ferritin (r = 0.815, p < 0.001 ), and aTPO (r = -0.491, p = 0.024 ). On multiple regression, the correlation between hepcidinEL and ferritin was confirmed (p < 0.001 ). Conclusions . SAT is accompanied by a significant increase in hepcidin, which reflects an acute-phase inflammatory process. Parameters of iron homeostasis improved significantly while inflammatory indices got lower following recovery. The potential role of hepcidin as a predictive factor of the risk of SAT relapse needs to be assessed in studies on larger groups of SAT patients.